2021
DOI: 10.1021/acs.jafc.1c02703
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analyses of Metabolomes and Transcriptomes Provide Insights into Flavonoid Variation in Grape Berries

Abstract: Flavonoids in grapes contribute the quality of the berry, but the flavonoid diversity and the regulatory networks underlying the variation require a further investigation. In this study, we integrated multi-omics data to systematically explore the global metabolic and transcriptional profiles in the skins and pulps of three grape cultivars. The results revealed large-scale differences involved in the flavonoid metabolic pathway. A total of 133 flavonoids, including flavone and flavone C-glycosides, were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Transgenic assays showed that MYB16 affects the regulation of anthocyanin and flavanol in apples [ 20 , 21 ], and this gene has also been reported as a major regulator of cuticle formation in apples [ 22 ]. MYB24 was reported to promote flavonoid biosynthesis through regulation of FLS1 gene expression in Arabidopsis thaliana [ 23 ] , and MYB24 also plays a role in flavonoid regulation in grape berries [ 24 ]. The MYB transcription factor MYB101 ( MD09G1109900), underpinning a significant region, was shown to play role in chalcone synthase (CHS) leading to flavonoid biosynthesis in Lotus japonicus [ 25 ] and Rosa rugosa [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic assays showed that MYB16 affects the regulation of anthocyanin and flavanol in apples [ 20 , 21 ], and this gene has also been reported as a major regulator of cuticle formation in apples [ 22 ]. MYB24 was reported to promote flavonoid biosynthesis through regulation of FLS1 gene expression in Arabidopsis thaliana [ 23 ] , and MYB24 also plays a role in flavonoid regulation in grape berries [ 24 ]. The MYB transcription factor MYB101 ( MD09G1109900), underpinning a significant region, was shown to play role in chalcone synthase (CHS) leading to flavonoid biosynthesis in Lotus japonicus [ 25 ] and Rosa rugosa [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Yan73 suggested that the accumulation of anthocyanin in esh tissue was probably due to speci c expression of the structural genes and TFs, which was coordinated and regulated by VvMYBA1 transcription activator and VvMYBC2-L1 transcription repressor (Xie et al, 2019). Comparing the metabolic and transcriptomic pro les of the skin and esh of three table grape varieties ('Kyoho', 'Wink', 'Italia'), it was found that besides anthocyanin, avonol and avanol were also different in a wide range, and MYB24, MADS5 and two ubiquitin proteins (RHA2) were suggested as promising candidates for regulating avonoids biosynthesis in grape (Lu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of phenols was conducted according to the methods described previously with modification (Zhang et al ., 2018; Lu et al ., 2021). Sample powder (0.3 g) was mixed with 15 mL 60% ethanol (v/v) and ultrasonically extracted at 60°C for 1.5 h. After centrifugation, the supernatant was collected for the determination of total phenol (TPC) and flavonoid content (TFC).…”
Section: Methodsmentioning
confidence: 99%